Phenylazo-BODIPYs: Direct Access via Pd-Catalysis - Röttger, Sebastian H.; Birk, Anjuli J.; Butschke, Burkhard; Jones, Peter G.; Werz, Daniel B. (Synlett, 2024)
A new type of functionalized BODIPY dyes is described. Utilizing an established procedure for Buchwald–Hartwig reactions, we have been able to convert α-chloro BODIPYs to α-azo-BODIPYs using phenylhydrazines. Optimization of the reaction conditions and variation of the BODIPY core and the phenylhydrazine were conducted. Absorption and emission spectra were recorded.
Keywords: BODIPY; azo group; dyes; phenylhydrazine; Buchwald–Hartwig coupling